2017
DOI: 10.1007/s40262-017-0582-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Optimization of Everolimus Dosing in Oncology: A Randomized Crossover Trial

Abstract: BackgroundThe mammalian target of rapamycin (mTOR) inhibitor everolimus is used in the treatment of breast cancer, neuroendocrine tumors, and renal cancer. The approved 10 mg once-daily dose is associated with considerable adverse effects and it has been suggested that these are associated with the maximum concentration (C max) of everolimus. Twice-daily dosing might be an alternative strategy with improved tolerability; however, a direct pharmacokinetic comparison of 10 mg once-daily with 5 mg twice-daily dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…The growth inhibitory effects of everolimus and gefitinib were analysed by XTT assay in three TNBC cell lines. The drug concentrations used in this study are close to the median peak plasma concentrations reported in clinical pharmacokinetics studies [31][32][33][34] . We examined the in vitro sensitivity of TNBC cell lines to increasing concentrations (0.1, 1, 10, 100 and 1000 nM) of everolimus alone (Fig.…”
Section: Resultssupporting
confidence: 64%
“…The growth inhibitory effects of everolimus and gefitinib were analysed by XTT assay in three TNBC cell lines. The drug concentrations used in this study are close to the median peak plasma concentrations reported in clinical pharmacokinetics studies [31][32][33][34] . We examined the in vitro sensitivity of TNBC cell lines to increasing concentrations (0.1, 1, 10, 100 and 1000 nM) of everolimus alone (Fig.…”
Section: Resultssupporting
confidence: 64%
“…Together with the recent study by Verheijen et al . , who showed that dose splitting everolimus 10 mg once daily in 5 mg twice daily resulted in lower maximum concentrations, our findings encourage a prospective study in cancer patients investigating everolimus 10 mg once daily vs . 3.75 mg twice daily in terms of noninferiority for efficacy and superiority for toxicity.…”
Section: Discussionsupporting
confidence: 75%
“…Improvement of formulation and dosing could be beneficial. A twice daily 5 mg dosing instead of once-daily 10 mg regimen conducted on a randomized pharmacokinetic crossover trial of everolimus suggested that such dosing could be promising to reduce adverse toxicity while maintaining treatment efficacy [370]. Nanoparticle-based mTOR targeting would need to be improved as well in order to have more specific effects on tumors and prevent undesirable cellular perturbations [371].…”
Section: Discussionmentioning
confidence: 99%